Four-year safety follow-up of the tetravalent dengue vaccine efficacy randomized controlled trials in Asia and Latin America. (July 2018) - Arredondo-García, J.L.; Hadinegoro, S.R.; Reynales, H.; Chua, M.N.; Rivera Medina, D.M.; Chotpitayasunondh, T.; Tran, N.H.; Deseda, C.C.; Wirawan, D.N.; Cortés Supelano, M.; Frago, C.; Langevin, E.; et al.
Abstract: Objective: Our objective was to describe the risk of hospital admission for virologically confirmed dengue (VCD) and the risk of clinically severe hospitalized VCD occurring up to 4 years after the first dose (years 1 to 4) in three randomized clinical trials comparing tetravalent dengue vaccine with placebo. Methods: The relative risks (RR) for hospitalized VCD from first dose to year 4 were estimated by year and age-group in individual and combined studies. Results: Overall, from Year 1 to Year 4, 233 and 228 participants had at least one episode of hospitalized VCD in the vaccinated ( n = 22 603) and placebo ( n = 11 301) groups, respectively (RR = 0.511, 95% CI 0.42–0.62). Among these, 48 and 47 cases, respectively, were classified as clinically severe. In children aged ≥9 years, 88 and 136 participants had at least one episode of hospitalized VCD in the vaccinated ( n = 17 629) and placebo ( n = 8821) groups, respectively (RR = 0.324; 95% CI 0.24–0.43). In vaccinated participants aged <9 years, particularly in those aged 2–5 years, there were more hospitalized VCD cases compared with the control participants in Year 3 but not in Year 4. The overall RR in those aged <9 years for Year 1 to Year 4 was 0.786 (95% CI 0.60–1.03), with a higher protective effect in the 6–8 year olds than in the 2–5 year olds. Conclusions: The overall benefit-risk remained positive in those aged ≥9 years up to year 4, although the protective effect was lower in years 3 and 4 than in years 1 and 2.